Efficacy and Side Effects of Granulocyte Collection in Healthy Donors - Brockmann, Franziska (S. Karger GmbH, 2013)
BACKGROUND: We report on the efficacy and side effects of granulocyte collection, which is comparatively infrequently performed in Germany. METHODS: Data from 378 healthy donors who underwent 914 granulocyte collections between 1999 and 2007 were retrospectively analyzed. Donors received G-CSF (lenograstim) at a median dose of 5.58 (3.25–7.36) μg/kg body weight with (n = 243) or without (n = 57) 4 mg dexamethasone. Side effects were recorded by donor monitoring and interview (questionnaire). RESULTS: The median granulocyte yield in apheresis products was 8.47 × 10(10) (3.07–14.92 × 10(10)). Granulocyte yields correlated significantly with gender, baseline WBC, PMN and PLT counts, and nicotine consumption. Dexamethasone and lenograstim administration was more effective than lenograstim administration alone (p < 0.001). Side effects of granulocyte mobilization were generally mild: bone pain in 31.4%, headache in 19.6%, and fatigue in 15.7% of donors. During follow-up (4 weeks), pruritus and/or exanthema were reported in 17.6% of donors. CONCLUSIONS: Granulocyte mobilization with lenograstim with or without dexamethasone was a safe and effective regimen for granulocyte mobilization. Side effects were tolerable and milder than those seen in peripheral blood stem cell donors. Long-term monitoring of granulocyte donors is important to establish optimal standards for the procedure.